Spherical inorganic powder and liquid sealing material

By using spherical inorganic powder with a specific particle size distribution, the problem of the accumulation of micropowder in semiconductor packaging materials is solved, and high fluidity and low cohesion are achieved, which improves production efficiency and reduces the risk of defects.

JP7657290B2Active Publication Date: 2025-04-04DENKA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023511121
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2022-03-24
Publication Date
2025-04-04
Estimated Expiration
2042-03-24

AI Technical Summary

Technical Problem

In semiconductor packaging materials with high filling rate, micropowders with small particle sizes are prone to aggregation, resulting in a decrease in fluidity and difficulty in penetrating into the gap between the chip and the substrate, affecting production efficiency, and may lead to semiconductor defects or short circuits.

Method used

A spherical inorganic powder with particle size distributions with at least two peaks is used, with a first peak between 0.1 μm and 0.6 μm and a second peak between 1.5 μm and 5.0 μm and a frequency ratio between 1.5 and 10.0 to reduce the cohesion of the powder in the resin while maintaining the fluidity of the resin.

Benefits of technology

It effectively prevents the increase of aggregation particles in the resin, maintains high fluidity and low cohesion, improves the production efficiency of semiconductor packaging materials and reduces the risk of defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657290000001
    Figure 0007657290000001
  • Figure 0007657290000002
    Figure 0007657290000002
Patent Text Reader

Abstract

[Problem] To provide an inorganic powder capable of giving a resin composition having excellent fluidity and capable of preventing an increase in agglomerated particles in a resin composition. [Solution] A spherical inorganic powder having, in a frequency particle size distribution, a first peak having a maximum value in the particle size range of 0.1-0.6 μm (inclusive), and a second peak having a maximum value in the particle size range of 1.5-5.0 μm (inclusive), the value of the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak being 1.5 to less than 10.0.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spherical inorganic powder and a liquid sealing material. [Background technology]

[0002] In recent years, in response to the trend of miniaturization, weight reduction, and high performance of electronic devices, the miniaturization, thinning, and high density of semiconductor packages are accelerating. In addition, the mounting method thereof is becoming more and more dominated by surface mounting suitable for high density mounting on wiring boards and the like. As such, as semiconductor packages and their mounting methods progress, semiconductor encapsulation materials are also required to have high performance, particularly improved functions such as solder heat resistance, moisture resistance, low thermal expansion, mechanical properties, and electrical insulation. In order to meet these requirements, resin compositions are used in which inorganic powders such as metal oxides, particularly amorphous silica powder, are filled into resin. It is desirable to fill the inorganic powders filled into the semiconductor encapsulation material with a high amount of the resin from the viewpoint of improving solder heat resistance, moisture resistance, low thermal expansion, and mechanical strength.

[0003] However, semiconductor encapsulation materials highly filled with inorganic powder have a problem that the fluidity decreases as the filling rate increases, making it difficult to penetrate into the gap between the chip and the substrate, resulting in a very poor productivity. In order to suppress the decrease in fluidity, a method is known in which a small amount of fine powder or ultrafine powder with a particle size of less than 1 μm is added to a large powder with a particle size of about several tens of μm or a medium powder with a particle size of about several μm. Patent Document 1 describes a spherical inorganic powder having a maximum particle size of 6 μm or less, a frequency particle size distribution showing a maximum diameter at least in the particle size range of 1 to 3 μm, and the ratio of the mode diameter to the median diameter and the coefficient of variation of the frequency particle size distribution each falling within a specified range. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-221224 A Summary of the Invention [Problem to be solved by the invention]

[0005] Fine and ultrafine particles are prone to agglomeration when preparing semiconductor encapsulation materials because their particle size is very small. If the agglomerated particles increase, it can cause poor dispersion. In such cases, the yield of the semiconductor encapsulation material can decrease and the semiconductor can become defective or short-circuited in the final product.

[0006] An object of the present invention is to provide an inorganic powder capable of preventing an increase in agglomerated particles in a resin composition. [Means for solving the problem]

[0007] The present inventors have conducted intensive research, thinking that it may be possible to prevent an increase in aggregated particles while preventing a decrease in fluidity by controlling the number and height of peaks in a frequency particle size distribution diagram. Surprisingly, they have found that an inorganic powder having at least two peaks in a predetermined particle size range in a frequency particle size distribution diagram and having a frequency ratio value at the maximum values ​​of the two peaks within a predetermined range can reduce the aggregation in a resin composition while maintaining the excellent fluidity of the resin composition. The inorganic powder designed in this way is a novel powder that has never been seen before. The present invention has the following embodiments. [1] A spherical inorganic powder having, in a frequency particle size distribution, a first peak having a maximum value in the particle size range of 0.1 μm or more and 0.6 μm or less, and a second peak having a maximum value in the particle size range of 1.5 μm or more and 5.0 μm or less, and in which the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak is 1.5 or more and less than 10.0. [2] The spherical inorganic powder according to [1], which has a minimum value in the particle size range of 0.4 μm or more and 1.0 μm or less in the frequency particle size distribution. [3] The spherical inorganic powder according to [2], wherein the ratio of the frequency at the minimum value of the first peak to the frequency at the maximum value is 0.9 or less. [4] A spherical inorganic powder according to any one of [1] to [3], wherein the ratio of the cumulative frequency of the second peak to the cumulative frequency of the first peak is 1.2 or more. [5] A spherical inorganic powder according to any one of [1] to [4], in which in a frequency particle size distribution, the cumulative frequency of particles having a particle size of 5.0 μm or more is 1.2% or less. [6] The spherical inorganic powder according to any one of [1] to [5], wherein the spherical inorganic powder is silica and the content of at least one selected from the group consisting of iron oxide, sodium oxide, calcium oxide, magnesium oxide, and potassium oxide is 50 ppm or less. [7] The spherical inorganic powder according to any one of [1] to [5], wherein the spherical inorganic powder is silica and has an alumina content of 200 ppm or more and 1300 ppm or less. [8] A liquid sealing material comprising the spherical inorganic powder according to any one of [1] to [7] and a resin. Effect of the Invention

[0008] According to the present invention, it is possible to provide an inorganic powder capable of preventing an increase in agglomerated particles in a resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] An embodiment of the present invention will be described in detail below. The present invention is not limited to the following embodiment, and can be implemented by making appropriate modifications within a range that does not impair the effects of the present invention. In this specification, the expression "X to Y" regarding a numerical range means not less than X and not more than Y.

[0010] [Spherical inorganic powder] The spherical inorganic powder according to this embodiment (hereinafter, simply referred to as "inorganic powder") has a first peak having a maximum value in a particle size range of 0.1 μm to 0.6 μm and a second peak having a maximum value in a particle size range of 1.5 μm to 5.0 μm in the frequency particle size distribution, and the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak is 1.5 or more and less than 10.0. Since the frequency particle size distribution has at least two peaks in the above-mentioned predetermined particle size range and the ratio of the frequency at the maximum values ​​of the two peaks is within the above-mentioned predetermined range, it is possible to prevent an increase in aggregated particles in the resin composition. In addition, when mixed with an inorganic powder having a large particle size of about several tens of μm or an inorganic powder having a medium particle size of about several μm, it is possible to prevent an increase in aggregated particles in the resin composition. The inorganic powder designed in this manner is a novel inorganic powder that has never been seen before, and the characteristics of having at least two peaks in a specified particle size range and the ratio of the frequencies at the maximum values ​​of the two peaks are very important factors in achieving both high fluidity of the resin composition and low coagulation of the inorganic powder in the resin composition.

[0011] The spherical inorganic powder has an average sphericity ((circularity)) calculated from the circularity of individual particles quantitatively and automatically measured using a particle image analyzer. 2 ) is preferably 0.85 or more. "Frequency particle size distribution" refers to the volume-based frequency particle size distribution. "Volume-based frequency particle size distribution" is measured by the laser diffraction scattering method (refractive index: 1.50) and is expressed by a distribution curve with the horizontal axis representing particle size (μm) and the vertical axis representing volume-based frequency (%). The volume-based frequency particle size distribution measured by the laser diffraction scattering method (refractive index: 1.50) is measured using a laser diffraction scattering particle size distribution analyzer (Beckman Coulter, "LS-230"), water (refractive index: 1.33) as the solvent, and a Tommy Seiko ultrasonic generator UD-200 (with ultra-micro tip TP-040 attached) at 200 W output for 2 minutes as pretreatment to disperse the particles.

[0012] The inorganic powder has a first peak and a second peak having a maximum value in a predetermined particle size range in the volume-based frequency particle size distribution. That is, the inorganic powder has at least two peaks including the first peak and the second peak in the volume-based frequency particle size distribution. If there is only one peak, it is not possible to prevent an increase in aggregated particles in the resin composition.

[0013] The term "peak" as used herein means a mountain-shaped curve having a boundary where the slope of the curve changes from positive to negative in the volume-based frequency particle size distribution. The particle size at the boundary is called the "maximum value" (μm). In this specification, the term "peak" does not include a shoulder (a portion where a bulge or step is formed in the middle of the slope of the curve constituting one peak). Each peak may have a shoulder, but from the viewpoint of filling the resin between the particles, each peak preferably does not have a shoulder. A peak begins at the rising part of the curve, passes through the maximum value (the apex of the mountain-shaped curve), and ends at the point where the frequency becomes 0, or the boundary where the slope of the curve changes from negative to 0 or positive.

[0014] The "first peak" refers to a peak having a maximum value in a particle size range of 0.1 μm to 0.6 μm in the volume-based frequency particle size distribution. The first peak has a maximum value in a particle size range of preferably 0.1 μm to 0.5 μm, more preferably 0.2 μm to 0.5 μm, and even more preferably 0.2 μm to 0.4 μm in the volume-based frequency particle size distribution.

[0015] The "second peak" refers to a peak having a maximum value in a particle size range of 1.5 μm to 5.0 μm in the volume-based frequency particle size distribution. The second peak has a maximum value in a particle size range of preferably 1.5 μm to 4.0 μm, more preferably 1.8 μm to 3.5 μm, even more preferably 1.8 μm to 3.0 μm, and particularly preferably 2.0 μm to 2.7 μm in the volume-based frequency particle size distribution.

[0016] The frequency at the maximum value of the first peak is preferably 0.5 to 5.0%, more preferably 0.5 to 3.0%, even more preferably 0.5 to 2.8%, still more preferably 0.7 to 2.7%, and particularly preferably 0.9 to 2.5%. By setting the frequency at the maximum value of the first peak to 0.5 to 5.0%, the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak can be easily adjusted to a predetermined range.

[0017] The frequency at the maximum value of the second peak is preferably 3.5 to 9.0%, more preferably 4.0 to 8.5%, even more preferably 4.5 to 8.0%, and particularly preferably 4.8 to 7.6%. By setting the frequency at the maximum value of the second peak to 3.5 to 9.0%, the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak can be easily adjusted to a predetermined range.

[0018] The ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak (frequency at the maximum value of the second peak / frequency at the maximum value of the first peak) is 1.5 or more and less than 10.0. If the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak is less than 1.5 or 10.0 or more, it is difficult to prevent an increase in aggregated particles in the resin composition. In addition, the flowability of the resin composition may decrease.

[0019] The ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak is preferably 1.7 to 9.5, more preferably 1.8 to 9.0, and further preferably 1.9 to 8.4.

[0020] The cumulative frequency of the first peak is preferably 5.0 to 50.0%, more preferably 10.0 to 45.0%, and further preferably 14.0 to 39.9%. By setting the cumulative frequency of the first peak to 5.0 to 50.0%, it is possible to easily adjust the ratio of the cumulative frequency of the second peak to the cumulative frequency of the first peak, which will be described later. The "cumulative frequency of the first peak" is the cumulative value of the frequency from the start point to the end point of the first peak.

[0021] The cumulative frequency of the second peak is preferably 50.0 to 95.0%, more preferably 55 to 90%, and further preferably 60.1 to 86.0%. By setting the cumulative frequency of the second peak to 50.0 to 95.0%, the ratio of the cumulative frequency of the second peak to the cumulative frequency of the first peak described below can be easily adjusted. The "cumulative frequency of the second peak" is the cumulative value of the frequency from the start point to the end point of the second peak.

[0022] The ratio of the cumulative frequency of the second peak to the cumulative frequency of the first peak (cumulative frequency of the second peak / cumulative frequency of the first peak) is preferably 1.2 or more, more preferably 1.3 to 7.0, and even more preferably 1.5 to 6.1. By making the ratio of the cumulative frequency of the second peak to the cumulative frequency of the first peak 1.2 or more, it is possible to easily achieve both high fluidity of the resin composition and low aggregation of the inorganic powder in the resin composition.

[0023] The inorganic powder preferably has a minimum value in the particle size range of 0.4 μm or more and 1.0 μm or less in the volume-based frequency particle size distribution. The inorganic powder may have a minimum value in the volume-based frequency particle size distribution, preferably in the particle size range of 0.5 μm or more and 0.9 μm or less, more preferably in the particle size range of 0.6 μm or more and 0.8 μm or less. A "minimum value" refers to the particle size of the valley between adjacent peaks in a volume-based frequency particle size distribution. A minimum value can be a boundary where the slope of the curve changes from negative to zero or positive. Therefore, if there is only one peak in a volume-based frequency particle size distribution, there is no minimum value.

[0024] The frequency of the minimum value is preferably 3.0% or less, more preferably 0 to 2.5%, further preferably 0 to 2.0%, and particularly preferably 0 to 1.7%.

[0025] The inorganic powder preferably has a ratio of the frequency at the minimum value of the first peak to the frequency at the maximum value of the first peak (frequency at the minimum value / frequency at the maximum value of the first peak) of 0.9 or less, more preferably 0 to 0.9.

[0026] In the inorganic powder, the cumulative frequency of particles having a particle size of 5.0 μm or more in the volume-based frequency particle size distribution is preferably 1.2% or less, and more preferably 1.0% or less.

[0027] The inorganic powder may have only the first and second peaks in the volume-based frequency particle size distribution, or may have one or more other peaks. The other one or more peaks may be present between the first and second peaks, may be present on the side of the particle size smaller than the first peak, or may be present on the side of the particle size larger than the second peak. When three or more peaks are present, any two of the peaks may be within the range specified in this embodiment. In one embodiment, the first peak and the second peak may be adjacent to each other (i.e., there are no other peaks between the first peak and the second peak). In one embodiment, there may be one or more peaks between the first peak and the second peak.

[0028] In the frequency particle size distribution diagram, the method of adjusting the frequency ratio value at the maximum values ​​of the two peaks to be within a predetermined range, such as by adjusting the size and classification of the raw material powder, as well as by adjusting the flame temperature and collection temperature during production, can be used.

[0029] (Inorganic powder) Examples of inorganic powders include metal oxide powders. Examples of metal oxide powders include inorganic powders such as silica (SiO2), alumina (Al2O3), titania (TiO2), magnesia (MgO), and calcia (CaO). The inorganic powder preferably contains one or more metal oxide powders selected from these, and more preferably contains silica. The inorganic powder is preferably a spherical inorganic powder, and more preferably spherical silica. In terms of bringing the thermal expansion coefficients of the semiconductor chip and the liquid encapsulant closer to each other, solder heat resistance, moisture resistance, and low wear of the mold, amorphous silica produced by a method of melting crystalline silica at high temperature is preferable.

[0030] The inorganic powder is silica, and the content of at least one selected from the group consisting of iron oxide, sodium oxide, calcium oxide, magnesium oxide, and potassium oxide is preferably 50 ppm or less, more preferably 40 ppm or less, and can be 5 to 40 ppm.

[0031] The inorganic powder is silica, and the alumina content is preferably 200 ppm or more and 1300 ppm or less, more preferably 300 ppm or more and 1000 ppm or less, and even more preferably 400 ppm or more and 700 ppm or less. The spherical silica powder having an alumina content of 200 ppm or more and 1300 ppm or less can be produced using raw materials derived from ores, and is therefore advantageous in terms of cost.

[0032] In order to further reduce agglomeration, the inorganic powder should have a specific surface area of ​​15 to 24 m2 as measured by the BET method. 2 The specific surface area measured by the BET method is preferably 17 to 22 m 2 / g, 20-22m 2 The specific surface area can be measured by the BET method using a specific surface area measuring device, for example, "Macsorb HM model-1208" (manufactured by Mountec Co., Ltd.).

[0033] (Volume-based cumulative diameter) Inorganic powder is a volume-based cumulative 50% diameter D 50 The volume-based cumulative 50% diameter D is preferably 1.2 to 2.8 μm. 50 " (also called "median size") is the particle size at which the cumulative value corresponds to 50% in the cumulative particle size distribution on a volume basis measured by the laser diffraction scattering method (refractive index: 1.50). The cumulative particle size distribution is expressed by a distribution curve with the particle size (μm) on the horizontal axis and the cumulative value (%) on the vertical axis. The cumulative particle size distribution on a volume basis measured by the laser diffraction scattering method (refractive index: 1.50) is measured using a laser diffraction scattering type particle size distribution analyzer (Beckman Coulter, "LS-230"), using water (refractive index: 1.33) as the solvent, and dispersing the particles for 2 minutes as a pretreatment by applying 200W output using Tommy Seiko's "Ultrasonic Generator UD-200 (with ultra-micro tip TP-040 attached)".

[0034] Volume based cumulative 50% diameter D 50 In one embodiment, the volume-based cumulative 50% diameter D 50 is 1.5 to 2.5 μm. Volume based cumulative 50% diameter D 50 The adjustment of can be made, for example, by adjusting the size or classification of the raw material powder. For example, in addition to adjusting the particle size of the raw material powder, classification (using a sieve classification or an air classifier) ​​after spheroidization can be performed to adjust the volume-based cumulative 50% diameter D 50 can be adjusted to.

[0035] Inorganic powder is a volume-based cumulative 10% diameter D 10 is preferably 0.1 to 0.3 μm, and more preferably 0.2 to 0.3 μm. 10 By setting the diameter of the particles to 0.1 to 0.3 μm, the particles can easily enter the gaps between large and medium-sized particles, allowing the particles to be packed more densely. Also, the amount of agglomerates can be reduced. 10 If it is too small, the flowability and moldability are easily impaired. Inorganic powder is a volume-based cumulative 25% diameter D 25 is preferably 0.1 to 2.0 μm, more preferably 0.1 to 1.0 μm, and further preferably 0.1 to 0.8 μm. 25 By adjusting the diameter D, the number of particles contained in the first peak is further optimized, and the effect of the present invention is further enhanced. 25 can be between 0.4 and 1.7. Inorganic powder is a volume-based cumulative 90% diameter D 90 The volume-based cumulative 90% diameter D is preferably 2.8 to 4.5 μm, more preferably 2.8 to 4.0 μm, and further preferably 3.2 to 4.0 μm. 90 By setting the diameter of the particles to 2.8 to 4.5 μm, the filling property can be improved and the fluidity can be significantly improved. 90 can be between 3.1 and 1.3. Inorganic powder is a volume-based cumulative 100% diameter D 100 The volume-based cumulative 100% diameter D is preferably 6.0 to 8.5 μm, more preferably more than 6.0 μm and not more than 8.0 μm, and further preferably 6.2 to 8.0 μm. 100 By setting the diameter D to 6.0 to 8.5 μm, it is possible to fill the gaps between the particles while obtaining an appropriate fluidity. 100 can be between 6.8 and 8.1. Volume based cumulative 10% diameter D 10 , cumulative 25% diameter D 25 , volume-based cumulative 90% diameter D 90 and volume-based cumulative 100% diameter D 100 are particle sizes at which the cumulative value is 10%, 25%, 90%, or 100% in the volume-based cumulative particle size distribution measured by a laser diffraction / scattering particle size distribution analyzer. The measurement method is the volume-based cumulative 50% diameter D 50 The adjustment method is the same as the volume-based cumulative 50% diameter D 50 In other words, in addition to adjusting the particle size of the raw powder, it is possible to obtain a 10% cumulative diameter D based on a specified volume by classifying the powder after spheroidization (by sieve classification or air classifier).10 , cumulative 25% diameter D 25 , volume-based cumulative 90% diameter D 90 and volume-based cumulative 100% diameter D 100 can be adjusted to.

[0036] (Method of manufacturing inorganic powder) The inorganic powder having the above-mentioned predetermined physical properties can be produced, for example, by crushing and classifying a commercially available ore as necessary, and then feeding it into a high-temperature flame to convert it into a fine spherical powder. This production method, for example, has the following steps. (i) if necessary, crushing and classifying the ore to obtain an ore powder (corresponding to an example of a raw material powder); (ii) feeding the ore powder into a high-temperature flame in a reaction vessel to form a fine spherical powder (molten powder); and (iii) optionally classifying and collecting the fine spherical powder;

[0037] Process (i) The ore used in step (i) is preferably high purity (e.g., 95% or more). Examples of the ore include silica sand, silica stone, titanium ore, magnesium ore, calcium ore, etc., and it is preferable to use one or more selected from these, and it is more preferable to use silica stone. The ore is pulverized using a pulverizer such as a vibration mill or a ball mill, so that an ore powder having a desired average particle size can be appropriately selected. The raw powder has a particle size (volume-based cumulative 50% diameter D 50 ) is preferably 3.0 to 7.0 μm, and more preferably 4.5 to 5.5 μm. A mixture of multiple types of raw material powders having different particle sizes can also be used.

[0038] Process (ii) In step (ii), the ore powder obtained in step (i) is injected into a high-temperature flame formed by a combustible gas and a combustion supporting gas using a burner, melted and spheroidized at a temperature above the melting point of the ore powder (for example, a temperature of 1800°C or higher in the case of silica (quartz stone)), and classified and collected while cooling to obtain a spheroidized powder (fine spherical powder). As the combustible gas, hydrocarbon gases such as acetylene, ethylene, methane, ethane, propane, and butane; hydrogen; gaseous fuels such as LPG and LNG; and liquid fuels such as kerosene and heavy oil; can be used. As the combustion supporting gas, oxygen, oxygen-rich cooling gas, and air can be used.

[0039] In addition, the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak can be adjusted by adjusting the melting temperature. For example, lowering the melting temperature reduces the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak. The melting temperature (flame temperature) is 1800 to 2200°C, more preferably 1900 to 2100°C, and further preferably 1950 to 2100°C. The melting temperature can be adjusted, for example, by the amount of gas and the amount of oxygen.

[0040] Process (iii) In step (iii), the fine spherical powder obtained in step (ii) is further classified and collected by a cyclone, sieving operation, etc., if necessary. By adjusting the powder collection temperature (the temperature of the bag filter when collecting the powder), the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak can be adjusted. For example, lowering the powder collection temperature increases the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak. The BET specific surface area can be adjusted by adjusting the powder collection temperature. For example, lowering the powder collection temperature increases the BET specific surface area. The powder collection temperature is preferably more than 100°C and less than 300°C, more preferably 120 to 290°C, even more preferably 150 to 280°C, and even more preferably 170 to 250°C.

[0041] (Application) The inorganic powder according to the present embodiment can be used for various applications. For example, it can be used for manufacturing materials such as semiconductor encapsulants. In particular, it can provide a resin composition with excellent flowability and prevent an increase in aggregated particles in the resin composition, so it can be preferably used for manufacturing semiconductor encapsulants for electronic devices.

[0042] [Inorganic composition] The inorganic composition according to the present embodiment includes the inorganic powder according to the above embodiment. Hereinafter, the inorganic powder according to the above embodiment is also referred to as "inorganic powder (P1)". The type and properties of the inorganic powder (P1) are as described above, so they will not be described here. Since the inorganic powder (P1) is composed of very fine particles, a small amount of this inorganic powder (P1) can be added to a large powder having a particle size of about several tens of μm or a medium powder having a particle size of about several μm to form an inorganic composition, so that even when the inorganic substance is highly filled (filled at a high content) in the resin, a resin composition having excellent fluidity can be obtained. In addition, the inorganic powder (P1) has at least two peaks in a predetermined particle size range in a frequency particle size distribution diagram, and the frequency ratio value at the maximum value of the two peaks is within a predetermined range, so that an increase in aggregated particles in the resin composition can be prevented.

[0043] In one embodiment, the mineral composition further has a volume-based cumulative 50% diameter D 50 Inorganic powder (P2) having a volume-based cumulative 50% diameter D 50 The resin composition may contain an inorganic powder (P3) having a particle size of 3 μm or more and less than 10 μm (preferably 3 μm or more and 8 μm or less, more preferably 4 μm or more and 6 μm or less). By containing such a large particle size inorganic powder (P2) and / or a medium particle size inorganic powder (P3), the solder heat resistance, moisture resistance, low thermal expansion property, and mechanical strength of the resin composition can be improved.

[0044] The types (compound types) of the inorganic powder (P2) and the inorganic powder (P3) are not particularly limited and can be selected from those exemplified as the inorganic powder (P1) according to the above embodiment. The types of the inorganic powder (P2) and the inorganic powder (P3) may be the same as or different from the inorganic powder (P1), independently of each other.

[0045] The content of the inorganic powder (P1) in the inorganic composition is preferably 0.1 to 30 mass%, more preferably 1 to 20 mass%, and even more preferably 3 to 20 mass%. By making the content of the inorganic powder in the inorganic composition 0.1 to 30 mass%, it is possible to provide a resin composition having excellent fluidity even when the inorganic composition is highly filled in the resin.

[0046] The content of the inorganic powder (P2) and / or the inorganic powder (P3) in the inorganic composition is preferably 70 to 99.9 mass %, more preferably 80 to 99 mass %, and even more preferably 80 to 97 mass % in total.

[0047] (Manufacturing method) The method for producing the inorganic composition is not particularly limited, and the inorganic composition can be obtained by mixing the inorganic powders by dry blending or the like using a known device.

[0048] (Application) The inorganic composition according to the present embodiment can be used for various applications. For example, it can be used for manufacturing materials such as semiconductor encapsulants. In particular, it can provide a resin composition with excellent flowability and prevent an increase in aggregated particles in the resin composition, so it can be preferably used for manufacturing semiconductor encapsulants for electronic devices.

[0049] [Resin composition (liquid encapsulant)] The resin composition according to the present embodiment contains a resin and the inorganic powder (P1) described above. Since the resin contains the inorganic powder (P1), it has excellent fluidity even when the resin is highly filled with inorganic substances. The type and physical properties of the inorganic powder (P1) are as described above, so they will not be described here.

[0050] The content of the inorganic powder (P1) in the resin composition is preferably 0.1 to 30 mass%, more preferably 1 to 20 mass%, and even more preferably 3 to 17 mass%. By making the content of the inorganic powder in the resin composition 0.1 to 30 mass%, it is possible to realize excellent fluidity even when the resin is highly filled with the inorganic substance.

[0051] In one embodiment, the resin composition further contains the inorganic powder (P2) and / or the inorganic powder (P3). The types and properties of the inorganic powder (P2) and the inorganic powder (P3) are as described above, and therefore will not be described here.

[0052] The content of the inorganic powder (P2) and / or the inorganic powder (P3) in the resin composition is preferably 65 to 95 mass%, more preferably 70 to 90 mass%, and even more preferably 70 to 87 mass%. By making the total content of the inorganic powders (P1) to (P3) in the resin composition 65 to 95 mass%, the resin is highly filled with the inorganic powders, and the solder heat resistance, moisture resistance, low thermal expansion, and mechanical strength of the resin composition can be improved.

[0053] (resin) Examples of the resin include epoxy resin, silicone resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyimide, polyamideimide, polyetherimide, and other polyimides, polybutylene terephthalate, polyethylene terephthalate, and other polyesters, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, etc. The resin preferably contains one or more selected from these, and more preferably contains an epoxy resin.

[0054] The epoxy resin is not particularly limited, and examples thereof include phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, epoxidized novolac resins of phenols and aldehydes, glycidyl ethers of bisphenol A, bisphenol F, bisphenol S, and the like, glycidyl ester acid epoxy resins obtained by reacting polybasic acids such as phthalic acid and dimer acid with epochlorohydrin, linear aliphatic epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, alkyl-modified polyfunctional epoxy resins, β-naphthol novolac type epoxy resins, 1,6-dihydroxynaphthalene type epoxy resins, 2,7-dihydroxynaphthalene type epoxy resins, bishydroxybiphenyl type epoxy resins, and further epoxy resins into which halogens such as bromine have been introduced to impart flame retardancy.

[0055] The resin preferably contains one or more epoxy resins selected from these, and more preferably contains an epoxy resin that is liquid at room temperature. Among these, the resin particularly preferably contains one or more epoxy resins selected from bisphenol-type epoxy resins such as bisphenol A-type epoxy resins and bisphenol F-type epoxy resins, and alicyclic epoxy resins.

[0056] The content of the resin in the resin composition is preferably 1 to 10 mass %, more preferably 2 to 9 mass %, further preferably 3 to 8 mass %, and particularly preferably 4 to 6 mass %.

[0057] (hardening agent) When the resin composition contains an epoxy resin, it is preferable that the resin composition further contains a curing agent. Examples of the curing agent include a novolac type resin obtained by reacting one or more mixtures selected from the group consisting of phenol, cresol, xylenol, resorcinol, chlorophenol, t-butylphenol, nonylphenol, isopropylphenol, octylphenol, etc. with formaldehyde, paraformaldehyde, or paraxylene under an oxidation catalyst, a polyparahydroxystyrene resin, a bisphenol compound such as bisphenol A or bisphenol S, a trifunctional phenol such as pyrogallol or phloroglucinol, an acid anhydride such as maleic anhydride, phthalic anhydride, or pyromellitic anhydride, and an aromatic amine such as metaphenylenediamine, diaminodiphenylmethane, or diaminodiphenylsulfone.

[0058] The content of the curing agent is preferably such that the hydroxyl equivalent (or acid anhydride equivalent) of the curing agent is 0.5 to 1.25 per 1 epoxy equivalent of the epoxy resin.

[0059] (Other additives) The resin composition may contain a curing accelerator, a release agent, a coupling agent, a colorant, etc., within the range not impairing the effects of the present invention. The curing accelerator is not particularly limited, and examples thereof include 1,8-diazabicyclo(5,4,0)undecene-7, triphenylphosphine, benzyldimethylamine, and 2-methylimidazole. Examples of the release agent include natural waxes, synthetic waxes, metal salts of straight-chain fatty acids, acid amides, esters, and paraffin. The coupling agent may be a silane coupling agent, such as epoxy silanes (gamma-glycidoxypropyltrimethoxysilane, beta-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes (aminopropyltriethoxysilane, ureidopropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, etc.), hydrophobic silane compounds (phenyltrimethoxysilane, methyltrimethoxysilane, octadecyltrimethoxysilane, etc.), and mercaptosilanes.

[0060] (Manufacturing method) The method for producing the resin composition is not particularly limited, and the resin composition can be produced by stirring, dissolving, mixing, and dispersing a predetermined amount of each material. The apparatus for mixing, stirring, dispersing, etc. of the mixture is not particularly limited, but a mortar and pestle machine equipped with a stirring and heating device, a three-roll mill, a ball mill, a planetary mixer, etc. can be used. These apparatuses may also be used in appropriate combination.

[0061] (Application) The resin composition according to the present embodiment can be used for manufacturing a semiconductor encapsulant. In particular, since the resin composition has excellent flowability and the inorganic powder is less likely to aggregate, it can be preferably used as a semiconductor encapsulant (liquid encapsulant) for electronic devices. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples, but the interpretation of the present invention is not limited to these examples.

[0063] [Production Example 1] Natural silica with a purity of 90% or more is crushed and classified into silica raw powder (50% cumulative diameter by volume D) using a vertical furnace with a burner installed at the top and a collection system (cyclone and bag filter). 50The silica particles (fine particle diameter: 4.8μm) were fed into a high-temperature flame formed by the combustion of LPG and oxygen, and melted and spheroidized to obtain spherical amorphous silica powder. The particles were classified using a sieve classifier or an air classifier to obtain spherical amorphous silica powder having the volume-based cumulative diameter and the maximum value of the peak in the frequency particle size distribution shown in Table 1. The powder collection temperature was set to 230℃.

[0064] [Manufacturing Examples 2 to 5] A spherical amorphous silica powder was obtained in the same manner as in Example 1, except that the powder collection temperature was set as shown in Table 1.

[0065] [Comparative Manufacturing Examples 1, 3-5, 7-8] A spherical amorphous silica powder was obtained in the same manner as in Example 1, except that the flame temperature and powder collection temperature were as shown in Table 1.

[0066] [Comparative Manufacturing Example 2] Silica raw powder (volume basis cumulative 50% diameter D 50 The procedure of Production Example 1 was repeated except that a powder collection temperature as shown in Table 1 was used.

[0067] [Comparative Manufacturing Example 6] Volume based cumulative 50% diameter D 50 Silica powder with a diameter of 1.0 μm and a volume-based cumulative 50% diameter D 50 The silica powder having a particle size of 0.1 μm was mixed with a silica powder having a particle size of 0.5 μm in a mass ratio of 8:2 using a vertical mixer to obtain a silica powder (mixed powder).

[0068] [measurement] (Volume based cumulative) The silica powders of Production Examples 1 to 5 and Comparative Production Examples 1 to 9 were dispersed using a laser diffraction scattering particle size distribution analyzer (manufactured by Beckman Coulter, "LS-230") with water (refractive index: 1.33) as a solvent for 2 minutes as a pretreatment, with an output of 200 W using an "ultrasonic generator UD-200 (with ultra-micro tip TP-040)" manufactured by Tommy Seiko Co., Ltd., to measure the cumulative particle size distribution measured by the laser diffraction scattering method (refractive index: 1.50). The cumulative 10% diameter D 10 , cumulative 25% diameter D25 , volume-based cumulative 50% diameter D 50 , volume-based cumulative 90% diameter D 90 , and the volume-based cumulative 100% diameter D 100 The cumulative frequency of the first peak and the cumulative frequency of the second peak were also calculated. The results are shown in Table 1.

[0069] (Frequency particle size distribution) For the silica powders of Production Examples 1 to 5 and Comparative Production Examples 1 to 9, a laser diffraction scattering type particle size distribution analyzer (manufactured by Beckman Coulter, "LS-230") was used, and water (refractive index: 1.33) was used as a solvent. As a pretreatment, a dispersion treatment was performed for 2 minutes using an ultrasonic generator UD-200 (with ultra-micro tip TP-040) manufactured by Tommy Seiko Co., Ltd., at an output of 200 W. The volume-based frequency particle size distribution measured by a laser diffraction scattering method (refractive index: 1.50) was measured, and the maximum value, the frequency at the maximum value, the minimum value, and the frequency at the minimum value were obtained, and the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak, the ratio of the frequency at the minimum value to the frequency at the maximum value of the first peak, and the ratio of the cumulative frequency of the second peak to the cumulative frequency of the first peak were calculated. The results are shown in Table 1.

[0070] The spherical amorphous silica powders of Production Examples 1 to 5 have two peaks with maximum values ​​in the particle size range of 3.0 μm or less. The two peaks are composed of a peak (first peak) with a maximum value in the vicinity of the 0.1 to 0.5 μm region and a peak (second peak) with a maximum value in the vicinity of the 2.0 to 3.0 μm region. The first and second peaks are adjacent to each other and neither has a shoulder. The frequency at the maximum value of the second peak is higher than the frequency at the maximum value of the first peak. The spherical amorphous silica powders of Production Examples 1 to 5 do not have a maximum value in the particle size range exceeding 3.0 μm, and do not have a frequency particle size distribution in the particle size range of 7.0 μm or more.

[0071] Between the first and second peaks, there is a boundary (minimum value) where the slope of the curve changes from negative to positive in the vicinity of the region of 0.5 to 1 μm. In detail, the spherical amorphous silica powder of Production Example 1 has a minimum value of particle size 0.7 μm and frequency 0.4%. The spherical amorphous silica powder of Production Example 2 has a minimum value of particle size 0.8 μm and frequency 1.6%. The spherical amorphous silica powder of Production Example 3 has a minimum value of particle size 0.6 μm and frequency 1.7%. The spherical amorphous silica powder of Production Example 4 has a minimum value of particle size 0.7 μm and frequency 0%.

[0072] (Measurement of impurities) The contents of Al2O3, Fe2O3, CaO, Na2O, MgO, and K2O were measured by the following method. Weigh out 1.0 g of sample onto a platinum dish, add 20 mL of hydrogen fluoride and 1 mL of perchloric acid, heat decompose on a sand bath, and concentrate until white smoke of perchloric acid is generated. After cooling to room temperature, transfer to a 25 mL measuring flask and dilute to the mark with water to make each analytical test solution. Separately, perform all the above procedures except for the sample to make a blank test solution. Then, measure the content of each by ICP atomic emission spectrometry.

[0073] [Table 1]

[0074] [Examples 1 to 11, Comparative Examples 1 to 10] In order to evaluate the properties of the resin compositions containing silica powder of Production Examples 1 to 5 and Comparative Production Examples 1 to 8, resin compositions were produced using the following materials. Resin: Biphenyl type epoxy resin (manufactured by Mitsubishi Chemical Corporation, "YH-4000HK") Hardener: Phenolic resin (manufactured by Meiwa Kasei Co., Ltd.) Curing accelerator: Triphenylphosphine Release Agent Silane coupling agent: epoxy silane (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM-403")

[0075] The resin compositions were produced as follows: The silica powders of Examples 1 to 5 and Comparative Examples 1 to 13 and the above materials were mixed in the components and ratios shown in Table 2 using a rotation-revolution type planetary mixer (Awatori Rentaro AR-360M; manufactured by Thinky Corporation) at a rotation speed of 2000 rpm and a revolution speed of 600 rpm for 10 minutes, and then vacuum degassed to obtain resin compositions.

[0076] The flowability of the resulting resin composition and the state of aggregation of the silica powder in the resin composition were measured and evaluated by the following methods. The results are shown in Table 2. (Liquidity assessment) The spiral flow value of each resin composition was measured using a transfer molding machine equipped with a spiral flow measurement mold in accordance with EMMI-I-66 (Epoxy Molding Material Institute; Society of Plastics Industry). The transfer molding conditions were a mold temperature of 175° C., a molding pressure of 7.4 MPa, and a pressure holding time of 120 seconds. A larger value (preferably 115 cm or more) indicates better fluidity.

[0077] (Evaluation of the agglomeration state: Measurement of the agglomeration content with openings of 75 μm or more) 100g of silica was weighed out and placed on a sieve with 75μm mesh. 1000mL of pure water was sieved through a shower nozzle for 30 seconds. The silica remaining on the sieve was collected in an evaporating dish and dried in a dryer, after which it was weighed and the percentage of residue was calculated. In the case of "Good", aggregation in the resin composition can be suppressed. The evaluation was based on the following criteria. 〇(Pass): 0.0%~2.0% △(Fail):2.0%~10% ×(Fail):10%~100%

[0078] [Table 2]

Claims

1. In a frequency particle size distribution represented by a distribution curve with the horizontal axis being the particle diameter (μm) and the vertical axis being the volume-based frequency (%), the particle size distribution has a first peak having a maximum value in a particle size range of 0.1 μm or more and 0.6 μm or less and a second peak having a maximum value in a particle size range of 1.5 μm or more and 5.0 μm or less, and the ratio of the frequency at the maximum value of the second peak to the frequency at the maximum value of the first peak is 1.5 or more and less than 10.0, A spherical inorganic powder in which the cumulative frequency of particles having a particle size of 5.0 μm or more is 1.2% or less in a frequency particle size distribution.

2. 2. The spherical inorganic powder according to claim 1, which has a minimum value in a particle size range of 0.4 μm or more and 1.0 μm or less in a frequency particle size distribution.

3. 3. The spherical inorganic powder according to claim 2, wherein the ratio of the frequency at the minimum value of the first peak to the frequency at the maximum value of the first peak is 0.9 or less.

4. The spherical inorganic powder according to any one of claims 1 to 3, wherein a ratio of the cumulative frequency of the second peak to the cumulative frequency of the first peak is 1.2 or more.

5. The spherical inorganic powder according to any one of claims 1 to 4, wherein the spherical inorganic powder is silica, and the content of at least one selected from the group consisting of iron oxide, sodium oxide, calcium oxide, magnesium oxide, and potassium oxide is 50 ppm or less.

6. The spherical inorganic powder according to any one of claims 1 to 4, wherein the spherical inorganic powder is silica and has an alumina content of 200 ppm or more and 1300 ppm or less.

7. A liquid sealing material comprising the spherical inorganic powder according to any one of claims 1 to 6, an inorganic powder having a volume-based cumulative 50% diameter D50 of 3 μm or more and less than 10 μm, and a resin, The content of the spherical inorganic powder in the liquid sealing material is 0.1 to 30 mass %.

Citation Information

Patent Citations

  • Silica-containing resin composition and its precision molding

    JP2003003074A

  • Spherical inorganic powder and use thereof

    JP2003221224A

  • Resin composition for semiconductor encapsulation and semiconductor device using the same

    JP2005239892A

  • Adhesive composition

    JP2007119662A

  • Microchip base plate made of glass, its manufacturing method and microchip

    JP2007132704A